Awareness and practice of standard treatment Guidelines and drug therapeutic committee Among primary care physicians - Dr.P.SARAVANAN,; Dr.V.KRISHNAN, (International Journal of Pharma and Bio Sciences, 2016)
This study was done to assess the awareness and practice of standard treatment guidelines (STG) among primary care physicians. To assess the concern, existence and participation of drug therapeutic committe among primary care physicians with affiliation to private or government health care. This was conducted as a cross sectional observational study surveyed across physicians Chennai after obtaining from our institutional ethics committee. Data was obtained using a validated questionnaire from allopathic physicians indulged themselves in private practice for at least five years. Study details were collected from physicians affiliated to either government or private institution for the last thirty-six months. Awareness, practice and status of academic training about STG were elucidated from everyone. Knowledge, existence and their participation in drug therapeutic committee (DTC) was collected only from physicians affiliated to any institution. Physicians with additional qualification were not invited for the study. Out of 220 physicians, 99 (47.1%) physicians had read a recent version of STG and 97 (46.1 %) physicians expressed they were able to practice current STG. Significant difference was seen between private and institution affiliated doctors in implementing STG (P-0.0245)(CI 1.386 ,0.799-2.406 ) .Similarly, the difference was significant between urban and semi-urban doctors in following STG (P 0.0200)(CI 0.477 , 0.255-0.895). Only 74 (34.2%) physicians had attended training for STG within one year. Only 19 of 133 (16.1 %) Physicians said that their institute has Drug therapeutic committee (DTC).:More training programme needed is among physicians to obviate the unawareness of standard treatment guidelines. Forming drug therapeutic committee in every institution is needed to uphold standard treatment practice at institutional level.